Living in Messy Times: An Interview with Kit Dobson. (1st June 2017) - Fitzpatrick, Ryan
Kit Dobson is an Associate Professor at Mount Royal University in Calgary where he works on Canadian literature, film, and art. He is the author of Transnational Canadas: Anglo-Canadian Literature and Globalization (2009), which tracks the development of globalization in Canadian literature. He is also the editor or co-editor of three more books: Please, No More Poetry: The Poetry of derek beaulieu (2013), Transnationalism, Activism, Art (with Áine McGlynn, 2013), and Producing Canadian Literature: Authors Speak on the Literary Marketplace (with Smaro Kamboureli, 2013). More recent work looks at the intersection of neoliberal governance and literary practice. In this interview, we discuss the political potentials of literature in a thickly material field, asking how it circulates amidst calls for social justice, how it helps code and decode spatial stability, and how it helps us map the effects and affects of global pressures on the individual subject.